The dynamics of TCAM integration in the Indian public health system: Medical dominance, countervailing power and co-optation. (October 2021) - Patel, Gupteswar; Brosnan, Caragh; Taylor, Ann; Garimella, Surekha
Abstract: Hierarchies of power among healthcare professionals are well documented, nonetheless, power remains neglected, understudied and under-theorised in health systems analysis and policy discussions, especially in the domain of Traditional, Complementary and Alternative Medicine (TCAM). Sociological and public health scholarship has documented the persistence of medical dominance in the health system, theorised as the limitation, subordination, exclusion and incorporation of other professions. This paper explores how interprofessional power dynamics shape the integration of TCAM into Indian primary healthcare centres, as part of a nationwide policy of TCAM integration and medical pluralism implemented since 2005. We conducted interviews (n = 37) with health system administrators, nurses, pharmacists, TCAM and biomedicine doctors, and observed day-to-day activities of primary healthcare centres for six months in Odisha state, India. Thematic analysis enabled the identification of themes and exploration of sub-themes. The analysis revealed multilayered forms of medical dominance within the primary healthcare system and identified multiple sites where everyday power is mobilised. Biomedicine practitioners exercised authoritative power and restricted TCAM doctors' access to facility-level resources, i.e. financial and workforce support, which inhibited the integration policy implementation. Significantly, TCAM doctors were 'ordered' to practice biomedicine at primary healthcare centres, which was beyond the scope of the integration policy. However, TCAM doctors were also able to exercise countervailing power in their day-to-day activities in the primary healthcare centres and sought to assist patients' health behaviour change through their authoritative knowledge about 'how to live a healthy life'. The health system actors involved in policy implementation hold a range of forms of power specific to the circumstances, influencing the integration processes. We explain these dynamics in relation to existing theories of medical dominance and countervailing power, while introducing a previously unreported dimension of dominance: 'co-optation', which enrols TCAM practitioners in the practice of biomedicine. Highlights: Medical dominance in Indian primary health care centres (PHCs) is multi-layered. AYUSH doctors working in PHCs experience subordination, exclusion and limitation. A new form of medical dominance – co-optation – was also uncovered in this setting. Co-optation here involved AYUSH doctors being ordered to undertake biomedical tasks. Via countervailing power, AYUSH doctors retained autonomy in community-based work.